PCOS we care the maintenance of Facebook support groups as safe spaces for women with PCOS - Guzman, Francesca Marie M.; Osorio, Maria Jeriesa P.; Lacdang, Danielle Anne (Quezon City University of the Philippines Diliman, 2025)
Polycystic Ovarian Syndrome (PCOS) significantly affects women’s well-being. In response, women turn to Facebook support groups as alternative safe spaces to seek and share information and support especially in the Philippines where access to healthcare is limited. This study explores how women with PCOS actively maintain these groups as safe spaces, addressing a gap in literature on the continuous need for maintenance of safety through user motivations, interactions, and affordance use. The study identifies four user roles: observers, learners, contributors, and critics, each playing a part in maintaining these groups as safe spaces. The study identifies four user roles: observers, learners, contributors, and critics, each playing a part in maintaining these groups as safe spaces. Through in-depth interviews and netnography, our findings reveal that women with PCOS joined Facebook support groups to cope with their unique struggles. They engage differently in the group based on their psychological safety, from silently reading posts to actively correcting misinformation. While lower safety is linked to less visible engagement, all roles contribute meaningfully to the group’s activity. Through these interactions, positive user relationships, collaborative dynamics, and shared group norms are fostered, guiding how members interact and support one another. Ultimately, these dynamics ensure that Facebook support groups continue to serve as vital safe spaces for women navigating the challenges of PCOS.
Thesis
Keywords: Polycystic ovary syndrome -- Psychological aspects; Online social networks -- Psychological aspects; Women -- Health and hygiene -- Psychological aspects; Facebook (Electronic resource) -- Social aspects